Computer networking concepts enhancement through analogies: a study of information technology students - Fathirma’ruf, Fathirma’ruf; Asmedy, Asmedy; Prayudi, Andi; Purwati, Diana; Sunarsi, Denok (Institute of Advanced Engineering and Science, 2024)
Computer networks are one of the skills that require mastering concepts, but a weak comprehension of these concepts can cause cognitive and psychomotor challenges for students. Several studies showed that a group of information technology education students at a university struggled with basic network practical exercises, signifying the importance of addressing conceptual understanding. Therefore, this study aimed to enhance students’ comprehension of high-level abstract computer network materials. To achieve the desired outcome, a pre-test post-test control group design was conducted on two groups of 29 students each. The results showed a positive impact on strengthening the conceptual understanding of students. Consequently, the experimental class achieved higher test scores compared to the control class, with a difference of 11.6. Data processing also showed higher N-gain values in the experimental class, indicating that analogies had a positive influence on students’ conceptual understanding of computer network materials.